Gluten Intake and Risk of Celiac Disease: Long-Term Follow-up of an At-Risk Birth Cohort. (August 2019) - Mårild, Karl; Dong, Fran; Lund-Blix, Nicolai A.; Seifert, Jennifer; Barón, Anna E.; Waugh, Kathleen C.; Taki, Iman; Størdal, Ketil; Tapia, German; Stene, Lars C.; Johnson, Randi K.; Liu, Edwin; et al.
Abstract : OBJECTIVES: To determine the association between the amount of gluten intake in childhood and later celiac disease (CD), for which data are currently scarce. METHODS: The prospective Diabetes Autoimmunity Study in the Young cohort includes 1875 at-risk children with annual estimates of gluten intake (grams/d) from age 1 year. From 1993 through January 2017, 161 children, using repeated tissue transglutaminase (tTGA) screening, were identified with CD autoimmunity (CDA) and persistent tTGA positivity; of these children, 85 fulfilled CD criteria of biopsy-verified histopathology or persistently high tTGA levels. Cox regression, modeling gluten intake between ages 1 and 2 years (i.e., in 1-year-olds), and joint modeling of cumulative gluten intake throughout childhood were used to estimate hazard ratios adjusted for confounders (aHR). RESULTS: Children in the highest third of gluten intake between the ages of 1 and 2 years had a 2-fold greater hazard of CDA (aHR 2.17; 95% confidence interval [CI], 1.22–3.88; P value = 0.01) and CD (aHR 1.96; 95% CI, 0.90–4.24; P value = 0.09) than those in the lowest third. The risk of developing CDA increased by 5% per daily gram increase in gluten intake (aHR 1.05; 95% CI, 1.00–1.09; P value = 0.04) in 1-year-olds. The association between gluten intake in 1-year-olds and later CDA or CD did not differ by the child's human leukocyte antigen genotype. The incidence of CD increased with increased cumulative gluten intake throughout childhood (e.g., aHR 1.15 per SD increase in cumulative gluten intake at age 6; 95% CI, 1.00–1.32; P value = 0.04). DISCUSSION: Gluten intake in 1-year-olds is associated with the future onset of CDA and CD in children at risk for the disease.